New directions in theorizing qualitative research : the arts - Denzin, Norman K.; Salvo, James (New Directions for Theorizing in Qualitative Inquiry Consists of Thematic Edited Volumes That Help Us Understand How to Put Qualitative Inquiry into Practice. the Chapters in Each Volume, from Established and Emerging Scholars, Represent New Directions fo., 2020)
New Directions for Theorizing in Qualitative Inquiry consists of thematic edited volumes that help us understand how to put qualitative inquiry into practice. The chapters in each volume, from established and emerging scholars, represent new directions for incorporating theory into justice-oriented qualitative research. The series is designed to reach a wide audience of scholars and students in the humanities and social sciences. The series aims to bring about experimental ways of reading lives so as to implement radical social change. The present volume takes arts-based research as its focus, emphasizing how these can be used to foster social justice.